2022
DOI: 10.7717/peerj.14261
|View full text |Cite
|
Sign up to set email alerts
|

Bioacoustic differentiation of calls in the chiffchaff complex

Abstract: The chiffchaff complex is a group of common forest bird species, notorious for the number of cryptic taxa recently discovered, being a great example of speciation in action. Vocalizations have been crucial to unveil its hidden diversity. In this study we quantitatively analyze the acoustic characteristics of their calls with permutational analysis of variance, canonical variate analysis and a self-organizing map, to determine their variability and differences. We related these differences with the geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…canariensis (Hartwig, 1886); P. sindianus Brooks, 1880). In contrast, the calls of the subspecies collybita and abietinus overlap to a large extent and appear to be indistinguishable in the field and on sonograms (Calviño-Cancela et al 2022).…”
Section: Vocalizationsmentioning
confidence: 82%
See 1 more Smart Citation
“…canariensis (Hartwig, 1886); P. sindianus Brooks, 1880). In contrast, the calls of the subspecies collybita and abietinus overlap to a large extent and appear to be indistinguishable in the field and on sonograms (Calviño-Cancela et al 2022).…”
Section: Vocalizationsmentioning
confidence: 82%
“…Calls of tristis and the Common Chiffchaff are therefore easy to identify in the field or on sonograms (Figure 1). Calviño-Cancela et al (2022), in their thorough call divergence analysis of all the taxa of the chiffchaff complex, showed that tristis has the most distinct calls of the complex, even more distinct than those of the Common Chiffchaff from the calls of other widely recognised species (P. ibericus Ticehurst, 1937;P. canariensis (Hartwig, 1886); P. sindianus Brooks, 1880).…”
Section: Vocalizationsmentioning
confidence: 99%
“…This specificity is then used to conduct a kinship analysis. Research on the use of this bioacoustics technique has been widely carried out by some previous studies [5]- [11], [20], [21] and has been applied in biological research on species diversity [26]. Therefore, this research will be very useful in conducting studies on indigenous local chicken species whose existence information needs to be known so that they can be appointed as one of the genetic resources which are one element of the biological wealth of a nation.…”
Section: F Discussionmentioning
confidence: 99%
“…Because this character then makes chickens can be grouped based on the uniqueness of their crows, people will recognize singer chickens, namely chickens with a unique crow sound, such as laughing chickens, pelung chickens, balenggek crows, bekisar chickens, gaok chickens and so on. Meanwhile, the father, who has the usual crowing sound, is not grouped into the type of singer chicken [18], [22]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic relationship and divergences of Phylloscopus have also been examined using multiple molecular markers such as mitochondrial genomes (mitogenomes) ( Yu et al, 2022 ), mitochondrial genes combined with nuclear segments ( Alström et al, 2018 ), and genome-wide data ( Zhang et al, 2021 ). Other research has also been carried out on leaf warblers, in relation to topics such as their biogeographic history ( Johansson et al, 2007 ), bioacoustic differentiation ( Calviño Cancela, Piña & Martín-Herrero, 2022 ), and migratory behavior ( Adams et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%